2014
DOI: 10.1111/jvp.12185
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, toxicology and therapeutics of mavacoxib in the dog: a review

Abstract: Mavacoxib is a novel nonsteroidal anti-inflammatory drug (NSAID), with a preferential action on the cyclooxygenase (COX)-2 isoform of COX and a long duration of action. It is classified chemically as a member of the sulphonamide subgroup of coxibs. Mavacoxib is highly lipid but very poorly water soluble. In the dog, the pharmacokinetic (PK) profile comprises very slow body clearance, long elimination half-life and a relatively large distribution volume. Biotransformation and renal excretion are very limited, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 61 publications
2
25
0
1
Order By: Relevance
“…For mavacoxib and meloxicam, EHR has been described in literature 19 , 21 , 26 , 33 , 34 . The present study was not able to demonstrate a pronounced presence of EHR in cockatiels, possibly due to the limited blood collection points at the secondary peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mavacoxib and meloxicam, EHR has been described in literature 19 , 21 , 26 , 33 , 34 . The present study was not able to demonstrate a pronounced presence of EHR in cockatiels, possibly due to the limited blood collection points at the secondary peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in dogs a low clearance and prolonged elimination half-life (t 1/2el ) are reported. Therefore a less frequent dosing is necessary, which contributes to an improved therapeutic compliance 19 21 . Initially, a classical dose determination study indicated that a dose of 4 mg/kg BW is necessary to exhibit clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Positive results from pre‐clinical and clinical trials, in which coxibs have been used as a preventative agent or as a therapeutic in combination with either chemotherapeutics or surgery, demonstrates the potential of using such drugs as cancer therapeutics . In veterinary medicine, mavacoxib (Trocoxil) is of interest because it is currently licensed to treat pain and inflammation associated with canine osteoarthritis where long‐term (up to 6 months) treatment is required . Mavacoxib is unique in the family of NSAIDs and coxibs as it exhibits a low clearance rate, a relatively large distribution volume and a long plasma half‐life, resulting in a reduced dosing regimen.…”
Section: Introductionmentioning
confidence: 99%
“…17,[30][31][32][33] In veterinary medicine, mavacoxib (Trocoxil) is of interest because it is currently licensed to treat pain and inflammation associated with canine osteoarthritis where long-term (up to 6 months) treatment is required. 34 Mavacoxib is unique in the family of NSAIDs and coxibs as it exhibits a low clearance rate, a relatively large distribution volume and a long plasma half-life, resulting in a reduced dosing regimen. Consequently, the potential clinical benefit of using mavacoxib is high.…”
mentioning
confidence: 99%
“…Additionally, NSAIDs have been reported to inhibit bone healing [55]. Recently, Lees et al [56] indicated that mavacoxib (Trocoxil, a selective COX-2 inhibitor) can be an alternative to NSAIDs that indiscriminately inhibit both COX-1 and COX-2. Of course, the use of mavacoxib also has limitations with regard to dog weight (contraindicated in dogs weighing <5 kg) and duration of treatment (not for >6.5 months).…”
Section: Introductionmentioning
confidence: 99%